Home-based music therapy - a systematic overview of settings and conditions for an innovative service in healthcare - Ostermann Thomas; Schmid Wolfgang (BMC, 2010)
Abstract Background Almost every Western healthcare system is changing to make their services more centered around out-patient care. In particular, long-term or geriatric patients who have been discharged from the hospital often require home-based care and therapy. Therefore, several programs have been developed to continue the therapeutic process and manage the special needs of patients after discharge from hospital. Music therapy has also moved into this field of healthcare service by providing home-based music therapy (HBMT) programs. This article reviews and summarizes the settings and conditions of HBMT for the first time. Methods The following databases were used to find articles on home-based music therapy: AMED, CAIRSS, EMBASE, MEDLINE, PsychINFO, and PSYNDEX. The search terms were "home-based music therapy" and "mobile music therapy". Included articles were analyzed with respect to participants as well as conditions and settings of HBMT. Furthermore, the date of publication, main outcomes, and the design and quality of the studies were investigated. Results A total of 20 international publications, 11 clinical studies and nine reports from practice, mainly from the United States (n = 8), were finally included in the qualitative synthesis. Six studies had a randomized controlled design and included a total of 507 patients. The vast majority of clients of HBMT are elderly patients living at home and people who need hospice and palliative care. Although settings were heterogeneous, music listening programs played a predominant role with the aim to reduce symptoms like depression and pain, or to improve quality of life and the relationship between patients and caregivers as primary endpoints. Conclusions We were able to show that HBMT is an innovative service for future healthcare delivery. It fits with the changing healthcare system and its conditions but also meets the therapeutic needs of the increasing number of elderly and severely impaired people. Apart from music therapists, patients and their families HBMT is also interesting as a blueprint for home based care for other groups of caregivers.